PENGARUH KOMITMEN ORGANISASI, IKLIM ORGANISASI DAN CAPACITY BUILDING TERHADAP KINERJA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN OGAN KOMERING ILIR - Tri Hayati Utami; Harun Syamsudin; Fakhry Zamzam (Integritas Jurnal Manajemen Profesional (IJMPRO), 2021)
This study aims to determine the results of the analysis of the effect of organizational commitment, organizational climate, and capacity building on the performance of the Ogan Komering Ilir Regency DPRD Secretariat. This research uses a confirmative survey method and is verification in nature. The method used is a quantitative method through data collection in the field and direct information from a sample of 71 people. The sample measurement refers to the concept of the Krejcie-Morgan table. The data collection techniques used questionnaires, interviews, observation and documentation. Hypothesis testing through t test and F test using SPSS analysis tools. The results of data processing using SPSS 20, using the t test that t count is 4.075 <t table 2.003 that organizational commitment has a positive and significant effect on performance; The organizational climate at the OKI Regency DPRD Secretariat apparently cannot affect the performance with t count 1.588> t table 2.003; Capacity Building affects the performance of the OKI Regency DPRD Secretariat with t count 2.176> t table 2.003. Regression determination jointly influences organizational commitment, organizational climate and capacity building on performance, in OKI Regency only 0.285 or 28.5%. This means that as many as 71.5% are influenced by variations or combinations of other variables outside the research variables. The conclusion of this research is that Organizational Commitment, Organizational Climate and Capacity Building on the Performance of the Regional Representative Council Secretariat of the Ogan Komering Ilir Regency are influential, but to improve the performance of the OKI DPRD Secretariat can be done by increasing the work commitment of employees; in carrying out the workload that is completed according to schedule, through increasing the organizational commitment of the DPRD Secretariat to guard against committing disgraceful acts in order to maintain the morale of the DPRD.